Surgical cotton microfibers loaded with nanoceria: A new platform for bone tissue engineering. Issue 1 (1st January 2023) - Singh, Sandhya; Bhushan, Sakchi; Das, Ankita; Barui, Ananya; Dutt, Dharm
Abstract: The number of bone damage/fractures has been increasing significantly over the world due to traumatic and accidental injuries. The process of bone regeneration is slowed by oxidative stress at the site of the bone defects. An increase in reactive oxygen species (ROS) is the major cause of oxidative stress. Polymeric scaffolds loaded with free radical scavenging material could be a promising new way to speed up bone healing. The redox-modulating property of cerium oxide (nanoceria) is well-known. In this study, nanoceria was integrated into cellulose-gelatin (CG) and freeze-dried to produce CG-NCs scaffolds. The impact of different concentrations of nanoceria on the physicochemical and biological aspects of scaffolds has also been investigated. FESEM revealed the presence of interconnecting pores in the scaffolds. Furthermore, adding nanoceria to the scaffolds improved mechanical, bio-mineralization properties, and decreased swelling and in-vitro weight loss. In vitro studies confirmed that CG-NCs scaffolds supported cell proliferation and differentiation better than bare (CG) scaffold. The findings of the DPPH assay show that CG-NCs can reduce free radicals. Finally, the antimicrobial evaluations imply that CG-NCs scaffolds successfully inhibited S. aureus and e.coli growth. Thus, the CG-NCs scaffold could offer a lot of potential in bone tissue engineering.